Nutritional Quality of Chicken Sausage with Addition of Tapioca Flour - Bulkaini Bulkaini; Djoko Kisworo; Sukirno Sukirno; Rani Wulandani; Maskur Maskur (Faculty of Animal Husbandry, University of Mataram, 2020)
The study was aimed to determine the effect of tapioca flour addition atvarious levels on the quality of chicken sausage. The research was design based on a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatment of tapioca flour addition level were: 0%, 10%, 20% and 30%. Data ofsausage quality were analyzed using Analysis of Variance and continued with Duncan's Multiple Range Test. The results showed that the addition of tapioca flour in the process of chicken sausage making were significantly affect (P <0.05) moisture and protein content, while the fat and ash content were not significantly effected (P> 0.05) by the treatment. The addition of 10% tapioca flour obtained the highest nutritional value of protein (17.67 Â± 0.93) % as compared to the other levels.